Wittgenstein on the human spirit - Lurie, Yuval. (Value Inquiry Book Series, 2012)
Wittgenstein on the Human Spirit provides a new understanding of Wittgenstein's discourse as an insightful philosophy of culture, pursued through self-reflection. It offers an edifying perspective on the conceptual underpinnings of culture as a shared expressive spiritual form of life. The ideas investigated in it are highly relevant for discussions in philosophy, aesthetics, anthropology, and cultural studies. The book embraces three studies: The Spirit of Jews , The Spirits of Culture and Civilization , and The Common Spirit of Human Beings . The first discusses Wittgenstein's remarks about Jews, focusing on their place within his philosophical thinking, self-reflection, and European discourse about culture and Jews. It shows how overcoming the anti-Semitic attitude implicit in them set off the major change in his philosophy. The second discusses Wittgenstein's reflections on the "deterioration of culture" in the modern period, showing how they are related to his remarks about following rules. The third discusses Wittgenstein's insights regarding the symbolic nature of myth, magic and religion. It suggests that modern human beings and those of ancient cultures possess a common expressive spiritual nature. This enables us to understand expressive practices in other cultures without interpretation. Nonetheless religious belief during the modern period is problematic.